Intrinsic Folding Proclivities in Cyclic β‐Peptide Building Blocks: Configuration and Heteroatom Effects Analyzed by Conformer‐Selective Spectroscopy and Quantum Chemistry. Issue 46 (25th September 2015) - Alauddin, Mohammad; Gloaguen, Eric; Brenner, Valérie; Tardivel, Benjamin; Mons, Michel; Zehnacker‐Rentien, Anne; Declerck, Valérie; Aitken, David J.
Abstract: This work describes the use of conformer‐selective laser spectroscopy following supersonic expansion to probe the local folding proclivities of four‐membered ring cyclic β‐amino acid building blocks. Emphasis is placed on stereochemical effects as well as on the structural changes induced by the replacement of a carbon atom of the cycle by a nitrogen atom. The amide A IR spectra are obtained and interpreted with the help of quantum chemistry structure calculations. Results provide evidence that the building block with a trans ‐substituted cyclobutane ring has a predilection to form strong C8 hydrogen bonds. Nitrogen‐atom substitution in the ring induces the formation of the hydrazino turn, with a related but distinct hydrogen‐bonding network: the structure is best viewed as a bifurcated C8/C5 bond with the N heteroatom lone electron pair playing a significant acceptor role, which supports recent observations on the hydrazino turn structure in solution. Surprisingly, this study shows that the cis ‐substituted cyclobutane ring derivative also gives rise predominantly to a C8 hydrogen bond, although weaker than in the two former cases, a feature that is not often encountered for this building block. Abstract : Probing local folding : Conformer‐ selective IR spectroscopy combined with quantum chemistry tools reveal the subtle details of the hydrogen‐bonding properties of four‐membered cyclic β‐peptide building blocks. Nitrogen‐atom substitution in the ring induces a hydrazino turn, a bifurcated C8/C5 bond with the N heteroatom lone electron pair playing a significant acceptor role (see figure).